New specific skeletal muscle mass index cut-offs for the assessment of sarcopenia in patients with severe obesity - Bufano, Annalisa; Cartocci, Alessandra; Benenati, Nicoletta; Ciuoli, Cristina; Simon Batzibal, Maria; Bombardieri, Alessio; Iraci Sareri, Gabriele; Sannino, Ida; Tirone, Andrea; Voglino, Costantino; Vuolo, Giuseppe; Castagna, Maria Grazia (Frontiers in Endocrinology, 2024)
Introduction: Bioelectrical Impedance Analysis (BIA) is the most used tool in clinical practice to evaluate body composition in patients with obesity. Skeletal muscle index (SMI) defined by BIA has been proposed for the identification of sarcopenia but there are not currently any univocal cut-offs about this condition. We aimed: (1) to determine the prevalence of sarcopenia in patients with severe obesity by using the current cut-offs of SMI, (2) to define a new specific cut-off, (3) to validate the new cut-off and (4) to re-determine the prevalence of sarcopenia. Methods: 300 patients, 74% female and 26% male, mean age 42.6±9 years, with morbid obesity (mean BMI 46.7± 6.5 kg/m2) followed by the Unit of Endocrinology from January 2014 to December 2020 were retrospectively evaluated. SMI was calculated as skeletal muscle mass normalized for squared height through the BIA equation by Janssen et al. Results: prevalence of sarcopenic obesity calculated with the cut-off points reported by De Rosa et al. (7.3 kg/h2 for females and 9.5 kg/h2 for males) was 2.3%. The prevalence of sarcopenia was calculated by using new cut-offs: with the cut-off obtained from standard deviation method (8.2 kg/h2 for females and 10.2 kg/h2 for males), a prevalence of 14.7% was observed, whereas with the cut-off calculated through K-means unsupervised cluster (9.2 kg/h2 for females and 11.3 kg/h2 for males), the prevalence reached to 47.6%. The new cut-offs were validated by a second sample consisting of 300 patients with morbid obesity (BMI 44.9±6.7 kg/m2): the rate of sarcopenic patients was still higher than the rate observed in the training cohort (56%); after the matching procedure (by BMI and age), the rate of sarcopenic patients was similar in both groups (50.2% in validation group and 53% in training group, p=0.6). Conclusions: the new cut-offs calculated with cluster analysis could better identify sarcopenia in morbidly obese patients. However, further studies are needed to validate these cut-offs in different patient cohorts.